Determination of passenger train reliability through travel delay. (March 2023) - de Rezende Francisco, Fábio; Sabino, Pedro Leite; Silveira Lopes, Luiz Antônio; Lopes da Silva, Paulo Afonso; Ferro, Newton José
Abstract: The objective of the present work is to demonstrate a methodology for assessment of passenger train reliability from the perspective of a KPI to measure the number of passengers whose travel time has been affected by delays. Based on this indicator, a workflow is proposed to select critical train subsystems and analyze their reliability using the probability distribution that best suits the available failure data. The proposed methodology was applied to the train fleet of the Rio de Janeiro Metro Concession, who was responsible for about 20% of the occurrences that affected the "passengers delayed" indicator in the period from May to December 2019, to evaluate the reliability of the doors subsystem, which was the most critical in terms of failures that affected passenger travel time in 2019 (145 failures). The results demonstrated a 66% drop in the subsystem reliability in five years, ratifying the feasibility and effectiveness of the methodology. The originality of this article is a result of the innovative proposal of a methodology to manage critical assets and systems by evaluating the effect of their failures on quality-of-service attributes valued by railway customers.